2011
DOI: 10.21065/19204159.3.179
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Thyroid Hormones Level in Premenopausal and Postmenopausal Females

Abstract: Thyroid dysfunction is the common endocrine disorder and females are more affected than males. The aim of this study was to assess the serum thyroid hormones level in premenopausal and postmenopausal females with thyroid dysfunction and observed the effect of thyroid dysfunction on body weight and menstrual regularity. Total 91 female subjects were included in the study. Serum thyroid hormone levels of TSH, FT3 and FT4 were assessed by ELISA technique. It was concluded from the present study that serum TSH lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…[10] This inhibits thyroid action and lowers the rate of metabolism in the body. Studies on the effect of menopause on thyroid function are commonly associated with reduced effective thyroid hormones, [11]- [13] and the fall in estrogen levels at menopause is linked to some disorders including cardiovascular diseases and the clinical presentation of pre-existing thyroid diseases, and other comorbidities. [14], [15] Increase in age and BMI has also been implicated in the changes in thyroid function.…”
Section: Introductionmentioning
confidence: 99%
“…[10] This inhibits thyroid action and lowers the rate of metabolism in the body. Studies on the effect of menopause on thyroid function are commonly associated with reduced effective thyroid hormones, [11]- [13] and the fall in estrogen levels at menopause is linked to some disorders including cardiovascular diseases and the clinical presentation of pre-existing thyroid diseases, and other comorbidities. [14], [15] Increase in age and BMI has also been implicated in the changes in thyroid function.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroidstimulating hormone (TSH) levels, particularly in females, may vary as a result of age-related changes in the body's regulatory mechanisms for thyroid hormone levels [3]. Additionally, there were few studies that showed the association of menopausal symptoms with thyroid disorders, while some studies did not demonstrate any correlation between menopausal symptoms with thyroid disorders [4][5][6]. Therefore, it is necessary to detect any abnormality in thyroid hormone levels in pre-and postmenopausal women so that early treatment can be initiated before the emergence of serious consequences.…”
Section: Introductionmentioning
confidence: 99%